Microtubule-associated protein 2 (MAP2) deficiency causes high-frequency hearing loss - Shin'ya, Kazuki T.; Miyasaka, Tomohiro; Ukaji, Takao; Harada, Akihiro; Kobayashi, Kohta I. (Frontiers in Audiology and Otology, 2025)
The role of microtubule-associated proteins (MAPs) in neuronal morphogenesis is well-investigated; however, their specific contribution to the sensory nervous system remains largely unexplored. In this study, we examined the role of MAP2 in auditory sensing, which critically depends on the cytoskeletal structure. Four-week-old Map2 homozygous knockout (Map2−/−) mice exhibited auditory sensitivity equivalent to that of wild-type mice. However, auditory brainstem responses (ABRs) revealed that 16-week-old Map2−/− mice exhibited a 30-dB reduction in hearing sensitivity, with a more pronounced effect at higher frequencies. The ABR wave V peak latency pattern showed a loss of non-linearity in 16-week-old Map2−/− mice. The latency of the ABR wave V further suggested that this reduction was not due to conductive hearing loss. Whole-mount cochlear immunostaining indicated that MAP2 was expressed in the cell bodies of cochlear inner hair cells (IHCs) and outer hair cells (OHCs) in wildtype mice. Notably, MAP2 expression in cochlear hair cells was higher in the basal region, Map2−/− mice had fewer OHCs in the base region, corresponding to high-frequency hearing aligned with ABR measurements. Furthermore, the density and morphology of spiral ganglion neurons were not affected by the loss of MAP2. These findings suggest that MAP2 contributes to the maintenance of hearing sensitivity and plays an important role in cochlear hair cells, particularly in the high-frequency range.